2021
DOI: 10.3389/fmolb.2021.693477
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circRNA_100146 Promotes Prostate Cancer Progression by Upregulating TRIP13 via Sponging miR-615-5p

Abstract: Objective: This study was conducted for investigating the functions of circular RNA circRNA_100146 (circRNA_100146) in the development of prostate cancer (PCa) and identifying the underlying mechanisms of the circRNA_100146/miR-615-5p/TRIP13 axis.Materials and Methods: Under the support of RT-PCR, the expression of circRNA_100146 in PCa cells was examined. Cell Counting Kit-8 (CCK-8) assays and clone formation assays were applied to the assessment of cell proliferation. We then determined cell invasion and mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…miR‐6165 can interact directly with IGF1R by binding to the 3ʹ‐UTR of IGF1R. Previous studies have shown that circRNAs, as miRNA sponges, regulate the expression of tumor regulatory genes through the circRNA–miRNA–mRNA axis 17–19 . In our study, we found that circ_0001459 sponged miR‐6165 to regulate the expression of IGF1R in HCC.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…miR‐6165 can interact directly with IGF1R by binding to the 3ʹ‐UTR of IGF1R. Previous studies have shown that circRNAs, as miRNA sponges, regulate the expression of tumor regulatory genes through the circRNA–miRNA–mRNA axis 17–19 . In our study, we found that circ_0001459 sponged miR‐6165 to regulate the expression of IGF1R in HCC.…”
Section: Discussionsupporting
confidence: 54%
“…For example, circ_0000337 promotes the cisplatin resistance of esophageal cancer via the miR‐377‐3p/JAK2 pathway, which might be a potential therapeutic target of esophageal cancer 17 . Circ_100146 acts as a tumor promoter in prostate cancer via the miR‐615‐5p/TRIP13 axis 18 . Circ_0089823 regulates SOX4 by sponging miR‐507, miR‐557, miR‐579‐3p, and miR‐1287‐5p, thereby enhancing the progression of non‐small‐cell lung cancer 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNA circGSE1 accelerated CC cell migration and invasion by acting as a sponge of miR‐138‐5p and increasing Vimentin expression level 28 . Circ‐CCDC66 could facilitate the malignant properties of CC cells by sponging miR‐452‐5p to enhance REXO1 expression 29 . Enforced expression of circHIPK3 promoted growth, migration, and invasion of CC cells by modulating the miR‐485‐3p/FGF2 axis 30 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 Circ‐CCDC66 could facilitate the malignant properties of CC cells by sponging miR‐452‐5p to enhance REXO1 expression. 29 Enforced expression of circHIPK3 promoted growth, migration, and invasion of CC cells by modulating the miR‐485‐3p/FGF2 axis. 30 He et al reported that hsa_circ_0018289 was positively correlated with the tumor size, lymph node metastasis, and stage of CC patients, suggesting that it was a promising biomarker for CC prognosis and disease monitoring.…”
Section: Discussionmentioning
confidence: 99%